PENERAPAN SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA (PERENCANAAN DAN PELAKSANAAN) TERHADAP SISWA SMK GONDANG WONOPRINGGO - Budiman, Febrian Arif; Sumbodo, Wirawan; Setiadi, Rizki; Rifa'i, Muhammad Arifian (Jurnal Pendidikan Vokasi Otomotif, 2024)
This study aims to describe the achievement of the K3 management system of class X11 TKR4 students with the dimensions of planning and implementation. The research was conducted in the TKR workshop of SMK Gondang Wonopringgo. The data collection technique used questionnaires, interviews, and documentation, the results were analyzed by categorizing each sub-indicator achievement and describing each sub-indicator. The results of the study obtained a planning achievement level of 49.15% in the poor category and the achievement of the implementation indicator of 52.8% so that it was categorized in the good enough category. The achievement of planning indicators includes sub-indicators of hazard identification with an achievement of 60% so that it falls into the category of good enough and sub-indicators of goals and programs with an achievement of 38.3% so that it falls into the category of not good enough. The achievement of implementation indicators includes sub-indicators of resources and responsibilities of 71.7%, communication and participation with students 42.2%, reporting and recording work accidents 45%, documentation of K3 letters 21.7%, purchasing goods and services 71.7%, work environment 75%, maintenance and repair of facilities 66.7%, health monitoring 82.2%, supervision 56.7%, first aid 35.8%, disaster emergency preparedness 13.3%.